STRATEGIES FOR IMPROVING THE PERFORMANCE OF HUMAN RESOURCES THROUGH AN ORGANIZATIONAL WORK PRODUCTIVITY - Elisabeth Tanti Pudiastuti; Sukmo Hadi Nugroho (JOURNAL ASRO, 2021)
One of the successes of a company in achieving its vision and mission is influenced by the quality of Human Resources (HR) in the company environment. The purpose of this study was to determine the importance and formulation of human resource management strategies and job satisfaction that have an impact on employee productivity. In this study, observing the application of Human Resources at the Management of Indonesian Company, based on service targets and operations. In this study, a questionnaire was prepared for respondents to be interviewed and the results were used to analyze the achievement of the HR performance at the company, namely the probability of company productivity. Furthermore, it can be identified what strategies the company undertakes to achieve its vision and mission. In the final section, it can be concluded that the quality of human resources needs to be improved according to the company's performance targets in achieving the company's vision and mission. Keywords: HR Management, HR Performance, Company Productivity